Serum lipids, oxidative stress, and systemic inflammation mediate the association between circadian syndrome and periodontitis - Zhang, Ruoyao; Han, Chong; Hu, Dijia; Chen, Qiukai; Zheng, Jinguo; Chen, Jiangshan; Okinaga, Toshinori (Frontiers in Nutrition, 2025)
BackgroundCircadian rhythm disruption is an underlying cause of metabolic syndrome (MetS) and is associated with the development of periodontitis. Circadian syndrome (CircS) is an emerging measure of circadian rhythm disruption based on MetS. We aimed to explore the cross-sectional association between CircS and periodontitis through the National Health and Nutrition Examination Survey 2009–2014.MethodsWe included 7,555 eligible participants. CircS was assessed by the five components of the MetS, depression, and short sleep duration, with fulfillment of ≥4 of the 7 components indicating the presence of CircS. Periodontitis was evaluated according to the Centers for Disease Control and Prevention-American Academy of Periodontology criteria. Multivariable logistic regression analysis was used to explore the association between CircS and periodontitis. In addition, restrictive cubic spline analysis, mediation analysis, and stratified analysis were used to comprehensively evaluate these associations.ResultsAfter adjusting for all confounders, CircS was significantly associated with periodontitis (odds ratio 1.509, 95% CI 1.326–1.716, p < 0.0001). Similar findings were found for CircS components. A higher number of components was associated with increased odds of periodontitis compared to participants without any components. However, among CircS participants, higher components were not associated with the odds of periodontitis. The number of CircS components was nonlinearly associated with periodontitis, and a positive association existed only when the number of components was <4. Mediation analyses suggested that several serum lipids, oxidative stress, and systemic inflammation markers mediated the association of CircS with periodontitis. This association was more pronounced in participants <60 years of age, income-poverty ratio >3, and non-vigorous physical activity.ConclusionThe presence of CircS was significantly associated with increased odds of periodontitis, serum lipids, oxidative stress, and systemic inflammation may mediate this association. These findings emphasize that CircS may serve as an independent risk factor for periodontitis and provide insights for individualized prevention of periodontitis.